The cross-cultural adaptation, reliability and validity of the instrument attitudes and knowledge of patient safety - Martinez Ramírez, Beatriz; Torres Soto, Nissa Yaing; Orozco-González, Claudia Nelly; Rojas Armadillo, María de Lourdes; Peña Torres, Edgar Fernando; Méndez-Domínguez, María Isabel (Horizonte Sanitario, 2023)
Objective: Patient safety seeks to reduce the risk and occurrence of avoidable harm, and to make errors less common in the population that receive health care. The training of human resources in health is considered a fundamental element to generate changes in health practices and contribute to reducing errors, furthermore safer processes. The objective of the present study is adapt and validate the "Questionnaire to measure attitudes and knowledge of patient safety" for its application with nursing and medical students of Public University of Medicine and Nursing in the Mexican Caribbean. Materials and methods: A cross-sectional, observational study, with the application of an anonymous and voluntary survey. The sample included 220 students (120 women and 100 men) with an average age of 24 years (SD=2) a Public University of Medicine and Nursing in the Mexican Caribbean. The 46% were undergraduate internship and 54% in Social Service practices. The instrument presented one identification card and 21 Likert-type items. Results: Through the Exploratory Factor Analysis (EFA), five factors were set with the Maximum Likelihood method and Varimax rotation on the 21 items of the patient safety questionnaire for Mexican students, resulting five factors that explain 63.59% of the total variance and an internal consistency index of the acceptable total scale (α=.87). Conclusions: The questionnaire to measure attitudes and knowledge about patient safety translated and adapted to medical and nursing students is valid, reliable and useful to measure patient safety actions for the prevention of errors in health care. Keywords: Patient safety; Validity; Reliability.